WikiBuild: A New Online Collaboration Process For Multistakeholder Tool Development and Consensus Building - Gupta, Samir; Wan, Flora T; Newton, David; Bhattacharyya, Onil K; Chignell, Mark H; Straus, Sharon E (JMIR Publications, 2011)
BackgroundProduction of media such as patient education tools requires methods that can integrate multiple stakeholder perspectives. Existing consensus techniques are poorly suited to design of visual media, can be expensive and logistically demanding, and are subject to caveats arising from group dynamics such as participant hierarchies. ObjectiveOur objective was to develop a method that enables multistakeholder tool building while averting these difficulties. MethodsWe developed a wiki-inspired method and tested this through the collaborative design of an asthma action plan (AAP). In the development stage, we developed the Web-based tool by (1) establishing AAP content and format options, (2) building a Web-based application capable of representing each content and format permutation, (3) testing this tool among stakeholders, and (4) revising this tool based on stakeholder feedback. In the wiki stage, groups of participants used the revised tool in three separate 1-week "wiki" periods during which each group collaboratively authored an AAP by making multiple online selections. ResultsIn the development stage, we recruited 16 participants (9/16 male) (4 pulmonologists, 4 primary care physicians, 3 certified asthma educators, and 5 patients) for system testing. The mean System Usability Scale (SUS) score for the tool used in testing was 72.2 (SD 10.2). In the wiki stage, we recruited 41 participants (15/41 male) (9 pulmonologists, 6 primary care physicians, 5 certified asthma educators, and 21 patients) from diverse locations. The mean SUS score for the revised tool was 75.9 (SD 19.6). Users made 872, 466, and 599 successful changes to the AAP in weeks 1, 2, and 3, respectively. The site was used actively for a mean of 32.0 hours per week, of which 3.1 hours per week (9.7%) constituted synchronous multiuser use (2-4 users at the same time). Participants averaged 23 (SD 33) minutes of login time and made 7.7 (SD 15) changes to the AAP per day. Among participants, 28/35 (80%) were satisfied with the final AAP, and only 3/34 (9%) perceived interstakeholder group hierarchies. ConclusionUse of a wiki-inspired method allowed for effective collaborative design of content and format aspects of an AAP while minimizing logistical requirements, maximizing geographical representation, and mitigating hierarchical group dynamics. Our method faced unique software and hardware challenges, and raises certain questions regarding its effect on group functioning. Potential uses of our method are broad, and further studies are required.